Analysis the Role of Parents’ in Online Learning Assistance for Students’ of Public Senior High School - Meidy Atina Kuron; Rasilemba Welua; Ester C. Wowor (Universitas Muhammadiyah Mataram, 2024)
The Covid-19 pandemic has been a valuable experience for all fields including education. This research aims to determine the role of Parents’ in accompanying students’ at Senior High School during online learning. The distribution of parental role scores and questionnaire item scores in online learning assistance is guided by norma correlation interval categorization. The research method used is a descriptive quantitative approach with actual conditions to describe the characteristics factually, systematically, and accurately of the variables studied. The results of this research conclude that the role of Parents’ in assisting students’ in online learning is optimal. The optimal achievement category being 67.39%, the quite optimal category being 17.3% and the very optimal category being 10.87%. The results of the questionnaire scores items on the role of Parents’ in assisting students’ learning show a very high category with 33.3% and the high category with of 36.7% which indicates that the role of Parents’ in several important circumstances has been carried out well and optimally. This statement is supported by students learning outcomes in science subjects, namely Physics, Chemistry, Biology and Mathematics, which are above the minimum completeness criteria. Parents' activities that make a high contribution to children's online learning include motivating children to be enthusiastic, supervising online lesson hours according to schedule, providing facilities in the form of devices and internet quota within reasonable limits. Monitoring techniques that are widely used by parents are building good communication with children, regarding online learning and reprimanding children when they do not follow online learning and assignments. Parents' involvement in science learning is done through the reinforcement given by parents to science learning.